2012
DOI: 10.1016/j.drugpo.2012.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the gendered patterns of substance use initiation among adolescents living in rural, central Mexico

Abstract: Background Little is known about the age of initiation and gender differences in substance use among adolescents in rural, central Mexico. Methods The cross-sectional data were collected from students enrolled in the Videobachillerato (VIBA) (video high school) program in Guanajuato, Mexico. Questionnaires asked students about the age at which they had used alcohol, cigarettes, or marijuana for the first time. Kaplan-Meier Survival Functions were used to estimate if males and females were significantly diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
1
2
0
1
Order By: Relevance
“…Overall, youth with migration intentions had nearly a doubling of the odds of having a drinking experience when compared to youth who reported no interest in living abroad. This finding confirms previous research conducted in Mexico (Marsiglia et al, 2011 , 2012 ). These previous studies found that the association between intentions to migrate and alcohol use varied by gender.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Overall, youth with migration intentions had nearly a doubling of the odds of having a drinking experience when compared to youth who reported no interest in living abroad. This finding confirms previous research conducted in Mexico (Marsiglia et al, 2011 , 2012 ). These previous studies found that the association between intentions to migrate and alcohol use varied by gender.…”
Section: Discussionsupporting
confidence: 93%
“…Most adolescents, however, are not old enough to have had prior migration experiences, which limits the implications of the previous studies examining the association between migration and substance use. Previous research has identified an association between intentions to migrate and alcohol use among adolescents residing in central Mexico (Marsiglia et al, 2011 , 2012 ). Stronger intentions to migrate among youth ages 14 to 24 was associated with greater access to drugs, drug offers, and illicit drug use (including marijuana, cocaine, and inhalants).…”
Section: Adolescent Alcohol Use In Mexicomentioning
confidence: 99%
See 1 more Smart Citation
“…La disparidad observada en la prevalencia del uso de drogas entre hombres y mujeres mexicanos también es consistente con las tendencias mundiales; sin embargo, advierten cómo esta brecha se viene estrechando en las generaciones más jóvenes. Las disparidades de género se explican por el efecto que ejercen los roles tradicionales, de modo que los entornos y las dinámicas de socialización ofrecen mayores oportunidades de consumo a los varones, al tiempo que restringen y estigmatizan más severamente esta práctica social entre las mujeres (UNODC, 2016;Malinowska-Sempruch, 2015;Ayers, Marsiglia, Hoffman, & Urbaeva, 2012;Kulis, Marsiglia, & Hecht, 2002).…”
Section: Discusión Y Conclusionesunclassified